Infrared Spectroscopic Evidence of WS2 Morphology Change With Citric Acid Addition and Sulfidation Temperature - Zavala-Sanchez, Luz A.; Maugé, Françoise; Portier, Xavier; Oliviero, Laetitia (Frontiers in Chemical Engineering, 2022)
MS2 morphology is strongly influenced by several parameters including the addition of a chelating agent and sulfidation temperature. In this work, we report the use of citric acid as chelating agent in order to prepare a series of WS2/Al2O3 catalysts that were submitted to sulfidation at several temperatures. The effect of these two parameters in the morphology of the slabs was explored by means of CO adsorption at low temperature followed by IR spectroscopy (IR/CO) and later confirmed by High-Resolution Scanning Transmission Electron Microscopy coupled with High Angular Annular Dark Field detector (HR STEM - HAADF). This allowed to depict the morphology of WS2 slabs by means of calculating the M-edge/S-edge site ratio. The use of citric acid in the preparation stage favors the increase of S-edge site concentration whereas it keeps that of M-edge sites: according to IR/CO, with an increasing amount of citric acid, the WS2 morphology progressively changes from a slightly truncated triangle exhibiting predominantly M edges to a hexagon with both M edge and S edge. In addition, HR STEM-HAADF demonstrated that the addition of citric acid in the impregnation step of W catalysts considerably reduces the size of WS2 nanoparticles increasing their dispersion degree. The morphology of the WS2 plates on the activated WS2/Al2O3 catalyst with a typical sulfidation temperature range (573–673 K) was detected to be a truncated triangle exposing both the M-edge and the S-edge. Furthermore, the IR/CO results indicate that the degree of truncation (ratio of S-edge/M-edge) of WS2 slabs gradually rises with the increasing sulfidation temperature. However, the most determining factor for a modification of the morphology of the slabs turns out to be the presence of citric acid as a chelating agent and not the sulfidation temperature. This change in morphology (i.e., change of S-edge/M-edge ratio) is a key factor for catalytic performance, since the M-edge and the S-edge show different reactivity in hydrodesulfurization (HDS) reactions. Notably, it was also found that the addition of citric acid not only improves the catalytic activity but also the stability of the catalysts, giving the best performance in concentrations higher than (CA/W = 1).